Delay in ludwig angina diagnosis is fatal - Siti Nidzwani Mohamad Mahdi,; Loo, SPS (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Ludwig angina is a fulminant condition that is potentially lethal. If left unrecognized or untreated, this condition carries a mortality rate of up to 50%. We illustrate a case of 43-year-old male who presented with signs and symptoms of Ludwig angina over a period of two days. The patient had history of tooth extraction prior to the onset of symptoms. Despite typical clinical presentation, Ludwig angina was not considered during the first visit to medical. Ludwig angina is a clinical diagnosis that requires high index of suspicion. Delay in the diagnosis increase the risk of airway obstruction due to its rapidly spreading oedema of the upper airway.